Myopic Versus Intertemporal Manipulation in Decentralized Planning Procedures - Laroque, Guy; Rochet, Jean-Charles (Review of Economic Studies, 1983)
Manipulation is studied in abstract planning procedures in exchange economies with private goods and a generalization of the results of Champsaur-Laroque (1980) is obtained. When the Nash equilibrium corresponding to myopic manipulation is unique, the outcome of consistent intertemporal manipulation on a time interval [0, T] is characterized. It is shown that when T goes to infinity, the resulting allocation tends towards a competitive equilibrium. For T equal to infinity, there exists a Nash equilibrium only when the initial allocation is Pareto-optimal.